Application and Theory of Petri Nets and Concurrency : 41st International Conference, PETRI NETS 2020, Paris, France, June 24–25, 2020, Proceedings /: 41st International Conference, PETRI NETS 2020, Paris, France, June 24–25, 2020, Proceedings. (2020) - Unknown
No abstract available